A Soundwalk in the heart of Poblenou superblock in Barcelona: Preliminary study of the acoustic events - Alsina-Pagès Rosa Ma; Ginovart-Panisello Gerardo José; Freixes Marc; Radicchi Antonella (Noise Mapping, 2021)
The Poblenou Superblock, in Barcelona, is a crucial element in the development of the new city-planning within the framework of the Superblock (Superilles) concept, whose principal aim is to recover the cultural, economic and social exchanges once produced in streets and squares. People living in urban areas need a lower traffic density, more green spaces and cleaner air in order to restore the previous uses of public spaces in their day-today lives. The urban actions conducted at this Superblock to change its uses were completed about 3 years ago, and neighbours and workers have already taken over the new spaces. In an interdisciplinary work on urban planning and acoustics, we detail the preliminary results of the acoustic events found in the recordings in a soundwalk in the heart of the Poblenou Superblock. Fifteen people evaluate and record sound fragments with the Hush City App application, in order to establish comparisons between the different points of the route, observe the spaces arranged for people and perceive the soundscape. Meanwhile, several acoustic technicians record 5-min long audios in the different stops designed for the soundwalk. The points chosen to make the recordings are very different from each other, some of them in the middle of gardens and others are on pacific streets and finally, we also wanted to include Superblock borders where the traffic is still very present. The results of our study were promising and have encouraged us to further investigate acoustics events in superblocks and include all the perceptual information provided by the Hush City App.